PWE-045 Should adenoma detection rates be age based?. (June 2019) - Choon, Xin Yi; Selby, Ian; Sayers, Ross; McNair, Alistair
Abstract : Introduction: Adenoma detection rate (ADR) is a measure of the quality of the colonoscopic examination, and in the UK a minimum target of 15% has been set for the whole population. Given the pathogenesis of adenomas, colonoscopists who examine a higher proportion of younger patients might be expected to encounter fewer adenomas, and as such not produce equivalent ADRs to those dealing predominantly with older patients. We set out to establish ADRs in patients of different age groups. Methods: We interrogated the endoscopy reporting system at a District General Hospital in South London over a 3-year period. We divided the patients into three age groups, and then determined the crude rate of polyp detection for each. From each age group we selected a sample of 100 consecutive patients who had polyps on their colonoscopy, and reviewed the histological diagnoses to determine the proportion of polyps which were clinically important i.e. adenomas, sessile or serrate lesions, and carcinomas. Chi-square testing was used to compare the different age groups for: the crude polyp detection rates, the rate of clinically important lesions in our samples, and the extrapolated number of clinically important lesions for the 3-year data set. Results: A total of 7928 colonoscopies were performed in this time period. Conclusions: Our data suggests there is a significant difference in ADRs in different age groups, and that clinically important polyps are more likely to be found in older people. This adds to the body of evidence that ADRs increase with age. Future key performance indicators for colonoscopies should take this into account.